Using a Harm Reduction Lens to Examine Post-intervention Results of Medical Abortion Training among Zambian Pharmacists - Fetters, Tamara; Raisanen, Keris; Mupeta, Stephen; Malisikwanda, Isikanda; Vwalika, Bellington; Osur, Joachim; Dijkerman, Sally (Reproductive Health Matters, 2015)
Despite broad grounds for legal abortion in Zambia, access to abortion services remains limited. Pharmacy workers, a primary source of health care for communities, present an opportunity to bridge the gap between policy and practice. As part of a larger operations study, 80 pharmacy workers, both registered pharmacists and their assistants, participated in a training on medical abortion in 2009 and 2010. Fifty-five of the 80 pharmacy workers completed an anonymous, structured training pre-test, treated as a baseline questionnaire; 53 of the 80 trainees were interviewed 12–24 months post-training in face-to-face interviews to measure the retention of information and training effectiveness. Survey questions were selected to illustrate the principles of a harm reduction approach to unsafe abortion. Bivariate analysis was used to examine pharmacy worker knowledge, attitudes and dispensing behaviours pre-training and at follow-up. A higher percentage of pharmacy workers reported referring women to a health care facility between surveys (47% to 68%, p = 0.03). The number of pharmacy workers who reported dispensing ineffective abortifacients decreased from baseline to end-line (30% to 25%) but the difference was non-significant. However, study results demonstrate that Zambian pharmacy workers have a role to play in safe abortion services and some are willing to play that role. © 2015
© 2015 Reproductive Health Matters
Keywords: Medical abortion; Pharmacists; Harm reduction; Zambia